Brinquedotecas: trajetórias e transformações - um estudo histórico - Silva, Bárbara Beatriz Pena da (2023)
A toy library is a place intended for toys and playful activities. Part of its history indicates that they are related to public spaces, such as toy libraries, and private spaces, such as playrooms in bourgeois family homes. The debate about this theme took on global aspects in the 1970s, stemming from exchanges between research and play practice centers located in different countries. This study aims to understand the discourses advocating for and studying the toy library over the years, both internationally and nationally, through the voices of those who propose to conceptualize it. Conducted as a historical study, the research involved seeking out and analyzing documents from international and national institutions, newspapers, magazines, specialized books (related to childhood and education), legislation, academic debates, processes of space standardization, and photographs. It comprehends that the idea of the toy library was constructed within the historical fabric of social relationships, through the material approach that traverses between people, institutions, devices, and rhetoric, in the manner that Thompson understands the idea of network formation through experience. The result is that toy libraries are entities focused on childhood, adaptable to social, cultural, and historical environments and immediate human needs: to alleviate poverty, heal, care, play, etc.